Determinants of Cross-Border Mergers and Acquisitions Performance of Chinese Enterprises - Zhang, Qi (2012)
The cross-border mergers and acquisitions (M&A) in developing countries such as China have become increasingly popular in recent years, but few papers focused on cross-border M&A from the view point of companies in developing countries. This paper is based statistics model to evaluate the major determinants of post Cross-Border M&A performance. Through quantitative evaluation and calculation, it will identify different kinds of factors in the model and find out whether and how these variables impact the research result simultaneously. This paper evaluates the extent to which these inside and outside factors will give a reference for the decision making of Chinese firms to merge oversea companies.